(untitled) (Research, Society and Development, 2021)
ProJovem Urbano/Prison in Piauí was implemented in two prisons: Women’s Penitentiary in Teresina and Regional Penitentiary Irmão Guido. The article is an experience report that aimed to describe an educational action of ProJovem Urbano/Prison held at the Regional Penitentiary Irmão Guido, Teresina, Piauí. The pedagogical activity was part of the Articulated Action Plan (PLA), prepared and executed under the guidance of educators of the curricular component in the areas of Language, Mathematics, Human Sciences and Natural Sciences, from January 2019 to January 2020. Development of the project took place in two stages: in the first; a diagnosis was carried out on the socio-environmental conditions of the prison system, entitled “Challenge Map”, based on the PLA booklet on causes and/or solutions to problems found in the Prison. In the second step; weeding, construction of new flower beds and choice of vegetables and medicinal plants took place. Eleven beds were built to grow the following vegetables: chives, coriander, peppers, lettuce, cabbage, carrots, tomatoes and medicinal plants such as mastruço, common grass, boldo, mint, lemon balm, basil, among others. Theoretical-practical educational actions contributed to the development of socio-emotional and cognitive skills, in addition to contributing to the process of re-socialization and social inclusion of re-educated students.